Improvement maintenance implementation based on downtime analysis approach. Issue 4 (10th October 2016) - Koussaimi, My Abdelbar; Bouami, Driss; Elfezazi, Saïd
Abstract : Purpose: Improvement maintenance's aim is identifying and implementing improvement action on equipment in service. The purpose of this paper is to propose an approach based on downtime's analysis to raise up equipment's performance, such as reliability, maintainability, availability, and safety. Steps of this approach will be illustrated by industrial applications. Design/methodology/approach: Furthermore, it proposes an approach based on a combination of several methods (FMECA, cause and effect diagrams, ABC analysis, 5W, RCA method, etc.). This approach is based on the downtime analysis and lead to improve maintenance's performance and equipment's reliability, maintainability, availability and safety. Those objectives have a strong correlation with the downtime. Findings: This approach led to apply easily improvement maintenance by using known methods. In the industrial application, this approach helps the authors to choose the good solution with the better life durance. Practical implications: After following the steps simulated by the proposed approach, actions and concrete measures will be deducted and illustrated by the industrial's application. Originality/value: At present, there is not an explicit improvement maintenance, to lead to specific maintenance actions on equipment in service, in order to improve the maintenance function goals.